Advances and Challenges in University Teacher Instruction in Intercultural Bilingual Education (2019)
This work constitutes an analysis and reflection on the university teacher instruction in the field of Intercultural Bilingual Education (IBE). This process is carried out at The University of San Carlos in Guatemala through the Escuela de Formación de Profesores de Enseñanza Media (EFPEM), an academic unit which, since 2002, has taken on this responsibility as a response to the training needs in this modality in the Guatemalan education and social system, within the framework of an education with cultural, ethnic and linguistic relevance. This initiative, originated through strategic alliances with national and international institutions, has made significant progress in the design and implementation of undergraduate and graduate programs. The methodology was based on information obtained from primary sources, a questionnaire, and interviews with students from the teacher instruction bachelor, and from the master in IBE, as well as with EFPEM graduates, teachers, and authorities; all of them, individuals with academic knowledge who have experienced the socio-cultural context of Guatemala. This study covers the period from the beginning of the university teacher instruction in IBE program to date. During this time, progress has been made in the design of careers that promote a highly relevant education, capable of satisfying at the national level, the needs of a multicultural, multiethnic and multilingual country such as Guatemala.